Proyecto de instrumentación y automatización del proceso industrial basado en la obtención de biodiesel - Guevara, Galo (2009)
The development of a program which objectives are based on the future convenience of having fuels from renewable resources, and having in counts the increasing world demand referred to the protection of the environment, doing emphasis between others in the reduction of the emission to the atmosphere of pollutant gases, they are valid arguments and of indisputable solidity as to plan and to develop action tending to contemplate this demand. As a contribution to the world problem and to the environmental impact that produces the use of fossil fuels and the need to produce the biofuels, in the project that we will detail later, we will present to an alternative fuel called Biodiesel; produced from matters of renewable bases; as an option for our country, as well as for the rest of the world of be supplying of fuel without this one has to be a derivative of the oil being able offer to us this way a better alternative not to contaminate the environment.